Estimated mortalities and potential yield of freshwater shark (Wallago attu) from the ’Dhir beel’ (riverine floodplain lake) ecosystem of the Brahmaputra basin, Assam, India - Goswami, P K; Devaraj, M (Indian Journal of Fisheries, 2011)
The annual instantaneous natural mortality as well as the total mortality rates and the potential yield of Wallago attu (Bloch and Schneider) were estimated from the ’Dhir beel’ ecosystem of the Brahmaputra basin, Assam, India. The instantaneous natural mortality (M) as estimated by different methods was found to be 0.83 (Pauly) and 1.15 (Cushing). However, the realistic value of M for W. attu in the ’Dhir beel’ was found to be 1.55 (assumed value). The average instantaneous total mortality (Z) values calculated by various methods were 3.44 (Jackson), 3.50 (Jones and Van Zalinge) and 3.70 (Beverton and Holt). The annual Z for the period 1980-’90 ranged from 1.45 (1988-’89) to 5.14 (1986-’87) for M = 0.83; 1.69 (1988-’89) to 4.95 (1986-’87) for M = 1.15 and 2.0 (1988-’89) to 4.67 (1986-’87) for M = 1.55. The potential yield per recruit (Y1) for W. attu in the ’Dhir beel’ was estimated to be 440.0 g corresponding to a length (1) of 70.80 cm and age (t) of 1.16 year as per the analytical model of Beverton and Holt. However, it was 427.78 g for 1 = 73.55 cm and t =1.22 year as per the Kutty and Qasim model. The biomass per recruit attained a peak at 1 = 62.63 cm and t = 0.98 year as per Jones’ length cohort analysis. The potential yield per recruit was estimated for three different values of natural mortality, M(=0.83, 1.15 and 1.55) as a function of exploitation ratio (E) for the observed age at first capture, t = 0.36 year corresponding to lc = 30.0 cm and also for the age at first recruitment, t = 0.21 year corresponding to lr = 17.5 cm. In view of the highly predatory habit, the length a-; first capture, lc = 30.0 cm can be considered to be the optimum size at first exploitation of W. attu in ’Dhir beel’. The maximum sustainable yield (MSY) for W. attu has been estimated to be 10,458 kg for the optimum effort at MSY (fmgy) of 182 men/day as per Schaefer and the MSY of 8,646 kg at fms of 182 men/day as per Fox. The fms of 182 men/day could be more economical for the W. attu fishery in the ’Dhir beel’.